Sulphuric Acid Digestion of Anatase Concentrate - Carolina Nogueira da Silva; Liliani Pacheco Tavares Nazareth; Mônica Elizetti de Freitas; Ana Claudia Queiroz Ladeira (Mining, 2024)
The processing of anatase ores by sulphuric acid digestion is well known for its low titanium dissolution yields, which makes the process economically and technically unfeasible. Anatase is considered much less reactive than other forms of titanium such as ilmenite and rutile. Generally, to enhance its dissolution, thermal processes along with acid and/or alkaline leaching processes are necessary. Studies of direct sulphuric acid digestion are few and the reported yields of titanium dissolution are <48%. This study investigated the main parameters of sulphuric digestion of anatase such as temperature, anatase:acid ratio, and time of reaction. Dissolution of titanium of around 86% were obtained at relatively mild conditions such as, temperature at 220 °C, grain size of 62 µm, an anatase:sulphuric acid ratio of 1:2, and 4 h of reaction. A comprehensive characterization of the resulting material indicated a content of 56.5% of TiO2 and 15% iron oxide—the main impurity. It also contained silica, aluminum, phosphorus, calcium, and rare earth elements (REE) in concentrations that varied from 1.61% to 6.01%.